TOSERBA RATU SEBAGAI UPAYA MENINGKATKAN RASA PERCAYA DIRI DAN HASIL BELAJAR MATEMATIKA MATERI POLINOMIAL - NORKHAMID NORKHAMID (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
The reason for choosing the title is because of the low self-confidence and mathematics learning outcomes of class XI MIPA 3 students. The purpose of this study was to increase self-confidence and mathematics learning outcomes in polynomial material for students of class XI MIPA 3 SMA Negeri 1 Mayong even Semester Academic Year 2017/2018 and to determine the magnitude of the increase in self-confidence and learning outcomes. This study took a sample of 38 students of class XI MIPA 3 in the even semester of SMA Negeri 1 Mayong in the academic year 2017/2018, consisting of 12 boys and 26 girls. The method used was Classroom Action Research consisting of 2 cycles, the data analysis used was comparative descriptive analysis by comparing data between cycles. The results of this study are the learning model